Menumbuhkan minat pelaku umkm dalam strategi pemasaran melalui digital marketing di Desa Pakis Kecamatan Bringin Kabupeten Semarang - Sundari, Yesi Ika; Sari, Anggy Lia Milfa; Qorni, Wais Al; Setianingrum, Sativa Wening; Bahjatulloh, Qi Mangku (Nur Science Institute, 2024)
Micro, Small, and Medium Enterprises (MSMEs) support the national and regional economy. In this digital era, the knowledge and expertise of Micro, Small, and Medium Enterprises (MSMEs) in the regions regarding technological developments and the application of digitalization in marketing strategies for a business are still very lacking, especially in Pakis Village. Marketing strategies classified as very traditional reflect the lack of understanding and knowledge about digital marketing. Socialization is carried out to increase the interest of MSMEs in marketing strategies through digital marketing. This socialization is carried out door to door or by visiting the houses of MSMEs. The lecture method is the method used in this socialization. This lecture method provides MSMEs with an understanding of digital marketing strategies through PowerPoint presentations. As a follow-up to support the work program for socializing marketing strategies through digital marketing for MSMEs, a business location sign is then made on Google Maps, and as a medium to promote brands or products, KKN students also put up banners for MSMEs so that the wider community better knows them.